ANALISA PENGARUH OZONISASI HASIL LUCUTAN PLASMA BERPENGHALANG DIELEKTRIK PADA BERAS TERHADAP PERUBAHAN AMILOGRAFI, KEKERASAN, DAN WARNA - Saifur Rijal; Muhammad Nur (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
The research on application of Dielectric Barrier Discharge Plasma with spiral-cylindrical configuration to produce ozone has been done. The purpose of this study was to determine the effect of ozone on the physical characteristics of rice which include discoloration, hardness, and the value of amilograph.Ozone reactor that used in this research have a spiral electrode made of wire, and dielectric material was pyrex tube. Plasma discharge was generated by AC high voltage up to 9 kV. Air flow rate used as a determinant of ozone concentration characteristic was 6 liters/min, while for treatment the air flow rate that used was 4 liters/min in order to obtain the ozone concentration of 10 ppm. Ozone is produced by inserting the free air into the reactor. Ozone concentration is determined by varying the voltage, while ozone generated is detected by ozone meter.The results showed that that the effect of ozonation to physical character of rice was not give significant changes and has a tendency to increase the quality of rice. It can be concluded that ozonation is safe for use in rice storage system. Keywords: Dielectric Barrier Discharge, spiral-cylindrical (SC), ozone, discoloration, hardness, value of amilograph.